Existence and Multiplicity of Positive Solutions for Fractional Differential Equation with Parameter (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, by using the fixed point theorem for a cone map, we study the existence and multiplicity of positive solutions for a class of fractional differential equation with parameter.
Keywords: Fractional differential equation; Green function; Cone.